Management of Comminuted Frontal Depressed Fracture Using Split Calvarial Graft: A Novel Technique - Maurya, Ved Prakash; Ranjan, Nitish; Ranjan, Ravi; Gupta, Shubham; Gupta, Mrityunjay Kumar; Patel, Tarun Kumar; Gaur, Nikhilesh Kumar; Bhaisora, Kamlesh Singh; Srivastava, Arun Kumar (Indian Journal of Neurotrauma, 2024)
Frontal depressed fracture generally results from high-speed motor vehicle accidents. The frontal fractures can be closed or open depending upon the involvement of the overlying skin. Frontal fracture can be comminuted if the bone is broken in at least two or more places. Because of the proximity of the frontal bone to critical structures like the frontal sinus, frontal dura with underlying brain parenchyma, and orbit with its content, an injury resulting in a frontal depressed fracture can result in a multitude of clinical symptoms. If not addressed promptly with an experienced team, these fractures can result in cerebrospinal fluid leak, osteomyelitis of the frontal bone, meningitis, and ocular and olfactory dysfunction with poor cosmetic outcomes. Thus, repairing the frontal depressed fracture should be considered a priority. The standard practice is to elevate the depressed fracture and repair any dural defect. In case of a comminuted fracture, elevation is not possible, and we generally remove the fracture pieces and repair the defect using titanium mesh. In this case report, we propose a novel technique of repair of the defect using a split calvarial graft, which is fashioned after separating the outer table from the inner table of the posterior frontal bone. This technique reduces the theoretical risk of infection and is cost-effective as our procedure does not require any external implant in cranioplasty.
Keywords: depressed fracture; split graft; calvarium; CSF leak; repair